Передумови виникнення професійних спілок в Україні та закону про професійні спілки - Верес, М.М. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Автор обосновывает положение о том, что деятельность профсоюзов в Украине в конце XIX - начале XX ст. основывалась на принципах самостоятельности, независимости, демократичности. Эти принципы легли в основу Закона Украины «О профессиональных союзах, их правах и гарантиях деятельности». Автор аргументирует, что опыт деятельности первых профсоюзов актуален и может быть использован в деятельности профессиональных союзов в независимой Украине. For the first time we offer proves this statement that Trade Unions in Ukraine at the end of the 1900th and the beginning of the twentieth century has begun their activities on the principles of independence and democracy. The Low of Ukraine «On Trade Unions, their Rights and Guarantees Activities.» The authorargues that the experience of the first Trade Union activities is actual today and can be used in the Independent Ukraine.